Analysis of the process of immersion of kernels in liquids with different specific mass - V. E. Saitov; V. G. Farafonov; A. V. Saitov (Аграрная наука Евро-Северо-Востока, 2019)
In a grain pile there is material other than grain including poisonous ergot sclerotia. Grain and sclerotia of ergot by linear dimensions and speed of soaring have similar characteristics. Complete separation of grain from ergot by these properties in a single process is impossible. Cleaning seeds from ergot sclerotia with the specific mass less than the specific mass of grain is possible in a salt solution. To mechanize the separation of ergot sclerotia from rye seeds by the wet method, there is an urgent need in the development of an appropriate device. Under study was an immersion in water (ρzh = 1.0∙103 kg/m3 ) and aqueous solutions of sodium chloride (NaCl) with a specific mass ρzh = 1.09∙103 and 1.15∙103 kg/m3 of individual rye grains with their specific mass ρz = 1.2...1.5∙103 kg/m3 , length lz = 5.0...10.0 10-3 m, width в = 1.4...3.6∙10-3 m and thickness δ = 1.2...3.5∙10-3 m. Theoretical studies were carried out on the basis of mathematical modeling methods using the laws of hydrodynamics, which were confirmed by experimental studies with winter rye grains of the Falenskaya 4 variety with a specific mass ρz = 1.1...1.3 103 kg/m3 , length lz = 5.0...8.0∙10-3 m, width в = 1.4...3.6∙10-3 m and thickness δ = 1.2...3.5∙10-3 m. It has been established that the calculated values of the immersion velocity of cylindrical kernels and spheroidal kernels in comparison with the experimental values in water (ρzh = 1.0∙103 kg/m3 ) is not more than 2%, and in aqueous solutions of sodium chloride (NaCl) the specific mass ρzh = 1.09∙103 and 1.15∙103 kg/m3 – 7 and 10%, respectively. This approach to determining the speed of immersion of grain in liquid can be used in the development of the machine for cleaning grain according to specific mass using wet method to substantiate its structural and technological parameters.